The impact of mindfulness techniques workshop on nursing professionals' self-awareness and emotional resilience in values-based healthcare - Kathwal, Jyoti; Sharma, Aditya; Sharma, Monika; Sharma, Kavita (International Journal Of Community Medicine And Public Health, 2025)
Healthcare environments are inherently demanding, often resulting in emotional fatigue and burnout among professionals. Self-awareness and emotional resilience are critical competencies for sustaining empathy, effective communication, and therapeutic relationships in such high-pressure settings. Mindfulness-based interventions, particularly those aligned with values-based healthcare (VBHC) principles, have shown promise in enhancing these attributes. This study evaluated the effectiveness of a two-day values-based meditation workshop in improving self-awareness, emotional resilience, and professional fulfillment among B. Sc. nursing students. A pre-experimental, pre-test/post-test design was utilized. Fifty-nine nursing students participated in a workshop integrating mindfulness meditation, reflective journaling, and cognitive reset exercises. Self-awareness and resilience were measured using a validated 31-point scale before and after the intervention. Qualitative data were collected through open-ended questions exploring spirituality, positivity, resilience, and life satisfaction. Post-intervention, the average self-awareness and resilience score increased significantly from 18.2 to 26.4 out of 31, with the proportion of high scorers (≥25) rising from 12% to 68% and low scorers (<15) dropping from 35% to 4%. Qualitative analysis revealed a strong association between self-awareness, positive mindset, and personal growth. The majority of participants recognized spirituality as integral to clinical practice and reported increased appreciation and cognitive control. Workshop feedback was overwhelmingly positive, and no significant correlation was found between age and outcome scores. Values-based meditation workshops are effective in enhancing self-awareness, emotional resilience, and professional fulfillment among healthcare professionals. The findings support the integration of mindfulness interventions into healthcare education to foster emotional intelligence, reduce burnout, and promote patient-centered care.